2019
DOI: 10.4269/ajtmh.18-0651
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Diagnosis of Cryptosporidiosis in Renal Transplantation in a Low-Prevalence Setting

Abstract: In high prevalence settings, cryptosporidiosis is commonly implicated as a cause of a gastroenteritis syndrome in the organ transplant population. Stool microscopy is predominant diagnostic modality. Therapeutic options in this group of patients are limited, making their management exceptionally challenging. We describe a case of a renal transplant recipient with cryptosporidiosis confirmed by the stool FilmArray gastrointestinal panel (GIP) nucleic acidbased assay and stool microscopy, describe our institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…including Cryptosporidium hominis and Cryptosporidium parvum . The extremely rare species of Cryptosporidium xiaoi, Cryptosporidium ryanae , and bovis are not picked up by it [ 5 ]. Despite being examined with only 18 positive clinical specimens, GIP's sensitivity and specificity for identifying cryptosporidiosis were 100% and 99.6%, respectively, in one of the biggest multicenter evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…including Cryptosporidium hominis and Cryptosporidium parvum . The extremely rare species of Cryptosporidium xiaoi, Cryptosporidium ryanae , and bovis are not picked up by it [ 5 ]. Despite being examined with only 18 positive clinical specimens, GIP's sensitivity and specificity for identifying cryptosporidiosis were 100% and 99.6%, respectively, in one of the biggest multicenter evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Stool FilmArray gastrointestinal panel (GIP) is also increasingly becoming popular owing to its quick turnaround time. 3 ICT has a disadvantage of detecting only C.parvum antigens and ELISA results need to be confirmed by mZN staining. In light of the above, microscopy continues to be the preferred method of diagnosis in low prevalence areas owing to its good sensitivity and specificity than other rapid diagnostic methods.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of the disease in the susceptible population is dependent on having a high index of suspicion especially in low-prevalence areas as routine stool sampling for ova, cysts, and parasites is not diagnostic. 3 Cryptosporidiosis is usually transmitted by poor sanitary conditions with low levels of personal hygiene and by ingestion of water tainted with human waste. Centers for Disease Control and Prevention (CDC) reports have shown that outbreaks due to this organism have increased even in the developed countries such as the United States owing to contamination of recreational and municipal water supplies.…”
Section: Introductionmentioning
confidence: 99%
“…Acid-fast staining, which has been used to detect cryptosporidiosis, is thought to miss many cases [ 10 , 29 ]. In recent years, increased use of antigen-detection assays and nucleic acid amplification are revealing more cases [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%